Water treatment using porous ceramics based on recycled diatomite and kaolin (2018)
The treatment of waters using filtering process through sintered porous ceramics based on diatomite and kaolin is reported. The water samples were prepared in low = 50%, medium = 100% and high = 150% concentrations, taking as reference point the maximum value allowed according to the resolution 2115 - 2007. The treated parameters were alkalinity; hardness to calcium, magnesium and total; chlorides; sulfates and total iron. The porous ceramics were formed by slip casting in plaster mold, from pastes with weight percentage of 50% recycled diatomite from the beer industry, 40% kaolin and 10% calcium carbonate. The particle sizes of the ceramic powders were the passed through ASTM 200 sieve. The drying of the ceramics was carried out at room temperature for 24 h, then by forced circulation oven Memmert UF-110 at 100 ° C for an equal time. The sintering of the ceramics was carried out in Vulcan D-130 electric muffle, at a maximum temperature of 1000 ° C for two hours, with a heating ramp of 10 ° C/min. The morphology of the ceramics was studied using scanning electron microscopy (SEM), while the physic ceramic analyses was evaluated according to ISO 10545-3 standard. Our results, reported what porous ceramics efficiency for the removal of chlorides up to 50%, while elimination of sulfates was approximately 43%, on the other hand, the total iron was removed up to 95%, likewise,it was evidenced that ceramics are not efficient in the treatment of hardness and alkalinity of waters with high concentrations